Peran Pengaruh Arsitektur Terapeutik dalam Meningkatkan Kesehatan Penghuni Rusunawa Depok - Palupi, Kirana Woro; Agustin, Dyan (Universitas Medan Area, 2025)
Mental and psychological health factors significantly influence daily life, and public housing plays a vital role in residents' well-being. By optimizing therapeutic architecture, it is expected that the overall comfort of residents, including mental, behavioral, spiritual, and psychological aspects, can be improved. This study uses a qualitative descriptive method, including literature review, field observation, and interviews, to investigate the impact of therapeutic architecture on physical and psychological health balance in public housing. The results show that design elements like green spaces, natural lighting, ventilation, and calming color schemes contribute to creating an environment that reduces stress and enhances comfort. This study reveals that the application of therapeutic architecture can improve both mental and physical health, ultimately leading to a better quality of life for residents